2009
DOI: 10.1038/hdy.2009.140
|View full text |Cite
|
Sign up to set email alerts
|

Direct mapping of density response in a population of B73 × Mo17 recombinant inbred lines of maize (Zea Mays L.)

Abstract: Maize yield per unit area has dramatically increased over time as have plant population densities, but the genetic basis for plant response to density is unknown as is its stability over environments. To elucidate the genetic basis of plant response to density in maize, we mapped QTL for plant density-related traits in a population of 186 recombinant inbred lines (RILs) derived from the cross of inbred lines B73 and Mo17. All RILs were evaluated for growth, development, and yield traits at moderate (50 000 pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 56 publications
3
31
0
Order By: Relevance
“…A similar study, also using a B73 3 Mo17 RIL population, identified QTLs associated with mature plant height in regions overlapping the 4.09 and 9.03 seedling QTLs. As in our study, it was the Mo17 parent that contributed the responsive allele (Gonzalo et al, 2010). In a separate study, the density response of several Tx303 3 B73 segmental introgression lines was evaluated (Gonzalo et al, 2006) and several density-dependent QTLs were identified, one of which mapped to 4.03, a location where we identified a QTL for first leaf sheath elongation under EOD-FR.…”
Section: Discussionmentioning
confidence: 99%
“…A similar study, also using a B73 3 Mo17 RIL population, identified QTLs associated with mature plant height in regions overlapping the 4.09 and 9.03 seedling QTLs. As in our study, it was the Mo17 parent that contributed the responsive allele (Gonzalo et al, 2010). In a separate study, the density response of several Tx303 3 B73 segmental introgression lines was evaluated (Gonzalo et al, 2006) and several density-dependent QTLs were identified, one of which mapped to 4.03, a location where we identified a QTL for first leaf sheath elongation under EOD-FR.…”
Section: Discussionmentioning
confidence: 99%
“…Several decades of breeding effort striving for consistent performance under high-density planting have dramatically increased the genetic gain in yield of this crop (Ribaut et al 1997;Li et al 2010;Gonzalo et al 2006Gonzalo et al , 2010. Most of the researchers have tried to map quantitative trait loci (QTLs) for grain yield traits under certain stress conditions such as plant response to water deficiency (Pelleschi et al 1999;Yue et al 2008;Lu et al 2006), nitrogen deficiency (Laperche et al 2007;Malosetti et al 2008), low phosphorus (Li et al 2010), and cold-temperature growing conditions (Zhang et al 2005, Han et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…A comparative study of commercial hybrids introduced from 1930 to 2001 showed an average increase in grain yield of 0.09 Mg ha -1 yr -1 (based on year of introduction of the hybrid) when hybrids were compared at 7.9 plants m -2 versus an average increase of only 0.014 Mg ha -1 yr -1 when hybrids were compared at 1.0 plants m -2 (Duvick, 2005). Numerous authors have examined the effect of plant density on relative differences among hybrids and other types of maize cultivars (Bavec and Bavec, 2002;Brekke et al, 2011aBrekke et al, , 2011bCarena and Cross, 2003;Carlone and Russell, 1987;Duvick, 2005;Duvick et al, 2004;Gonzalo et al, 2010;Russell, 1974Russell, , 1984Russell, , 1986Russell, , 1991Sangoi et al, 2002;Seka and Cross, 1995;Singh et al, 2011;Tollenaar, 1992;Widdicombe and Thelen, 2002). However, in few of the cited papers have environmental effects and genotype ´ environment interactions (G ´ E) for density response been addressed in great detail.…”
Section: Researchmentioning
confidence: 99%
“…However, none of the three studies provided convincing evidence that G ´ E exist for plant density response for maize grain yield. Several other studies included factorial combinations of genotypes, environments, and densities and did not fully analyze the factorial structure or simply did not find significant interactions between densities and environments or among G ´ E ´ density (Carena and Cross, 2003;Carlone and Russell, 1987;Cox and Cherney, 2012;Gonzalo et al, 2010;Hernández et al, 2014;Mansfield and Mumm, 2013;Porter et al, 2013;Sangoi et al, 2002;Tollenaar, 1992;Widdicombe and Thelen, 2002). At least one other author stated that significant G ´ E ´ density interaction was found, but provided no additional detail (Bavec and Bavec, 2002).…”
Section: Introductionmentioning
confidence: 99%